CMR assessment of epicardial edipose tissue in relation to myocardial inflammation and fibrosis in patients with new-onset atrial arrhythmias after STEMI - Yanfei Ren; Xinjia Du; Maochen Li; Lei Chen; Jiahua Liu; Yixuan Wu; Yuan Lu (BMC Cardiovascular Disorders)
Abstract Background Previous studies have shown that epicardial edipose tissue(EAT) appears to be associated with myocardial inflammation and fibrosis, but this is not clear in patients with new-onset atrial arrhythmias after STEMI. The present study focused on using CMR to assess the association of epicardial fat with myocardial inflammation and fibrosis and its predictive value in patients with new-onset atrial arrhythmias after STEMI. Methods This was a single-centre, retrospective study. We consecutively selected patients who completed CMR during their hospitalisation for PCI after STEMI from May 2019-January 2023, and then underwent regular follow-up, grouped by the presence or absence of new atrial arrhythmias, and enrolled patients were divided into atrial arrhythmia and non-atrial arrhythmia groups. Results In the atrial arrhythmia group, age, heart rate, Peak hs-TnT, PeakNT-proBNP, EATV, LAES, LAED, T1 native, T1*, ECV, and T2 were higher than those in the non-atrial arrhythmia group, and LVEF was lower than those in the non-atrial arrhythmia group. EATV showed a positive and significant correlation with T1native, T1*, ECV, and T2. (T1 native: r = 0.476,p < 0.001; ECV: r = 0.529,p < 0.001; T1*: r = 0.467,p < 0.001; T2: r = 0.538,p < 0.001). Multifactorial logistic regression analysis showed age, LVEF, EATV, T1*,ECV, T2 as independent risk factors for atrial arrhythmia. (p < 0.05) ROC analysis showed that the AUC for age was 0.568; AUC for LVEF was 0.656; AUC for EATV was 0.768; AUC for ECV was 0.705; AUC for T1* was 0.612; and AUC for T2 was 0.772. Conclusion In patients with STEMI, EAT is associated with myocardial inflammation, fibrosis. Age, LVEF, EATV, T1*,ECV, T2 are independent risk factors for new onset atrial arrhythmias and have good predictive value.